Análise da evolução da sustentabilidade municipal no cariri paraibano através do Índice de Desenvolvimento Sustentável para Municípios – IDSM - Luiz, Álisson Batista (2019)
Given the scenario of coexistence with the paradigm of how to develop without going beyond the limits of the environment, characterized by the degradation of environmental quality, it is clear that the development consciousness has emergence of change. A development is needed that calls for harmony between the various pillars that sustain society, cherishing the wellbeing of present and future generations. This development is considered a challenge for all of society, especially for public policy makers and managers, who, through environmental management, have the goal of maintaining a healthy environment for all generations, preserving and managing economic and social activities. social rights. Thus, for an efficient environmental management, it is necessary to monitor the level of sustainability through sustainability indicators, thus being able to evaluate the consequences of the development model and providing subsidies for good decision-making and for the definition of adequate public policies. The objective of this paper is to analyze the evolution of sustainability in the 29 municipalities that are part of the Cariri region of Paraíba, using the methodology "Sustainable Development Index for Municipalities" of Martins & Cândido (2008), justifying the contribution with the Paraíba cariri, a region located in the Brazilian semi-arid region, considered an extremely vulnerable area. Its development took place through the collection of secondary data in different periods, feeding the matrix of indicators and variables, applying the IDSM methodology, thus achieving the generation of indexes and situations in critical, alert, acceptable and ideal scale, resulting in evolutionary comparison of sustainability by size and general in the municipalities between the two periods. As a result, it was observed that, despite the positive evolution in many of the municipalities of Cariri in the periods studied, the situation inspired attention, since, although the general IDSM did not present a fall, a large number of municipalities were in a situation of alertness and addressing an area as important as sustainability, the search for optimization of indexes should be the main agenda of public managers and actions in public policies